MEDICT: A Malay<-> English bilingual dictionary for Java mobile phones - Devaraju, Anusuriya; Nahar, Haniza; Marimuthu, Sivasakti (2007)
Today, mobile phones provide number of advanced functions, among which possibility of running mobile applications seems to be the most interesting feature. It changes a standard mobile phone into a mini-size yet still powerful computer that able to run various applications, for example games, stock checkup, map guide, dictionary and so on. This paper presents a project currently in progress which aims at the construction of bi-directional Malay - English translation dictionary named MEDict. MEDict is an easy-to-use mobile dictionary that is the ideal reference tool for all those requiring quick access to word translations. MEDict will ideally suit J2ME mobile phones with GPRS connectivity. This paper delivers the initial development progress of MEDict. It covers the functional requirements and possible development approaches followed in building MEDict. The project incorporates the development of four main components: (1) a java-based mobile client that provides interface for front-end query input; (2) a back-end database for serving dictionary contents; (3) a dictionary service for handling the exchange between the mobile client's queries and the database; (4) a web system that allows the administrator to manage the dictionary contents. The key contribution of this study is the use of Java and mobile technologies to develop a translation dictionary between two languages that has not been previously supported. The developed mobile dictionary is expected to meet the needs of a wide range of users such as language learners, native speakers, travelers and business professionals in Malaysia.